Argument and evidence : critical analysis for the social sciences - Phelan, Peter, 1941- (Routledge, 1996)
Phelan and Reynolds' book is for anyone who needs to evaluate arguments and interpret evidence. It deals with the most fundamental aspects of academic study: * the ability to reason with ideas and evidence* to formulate arguments effectively* to appreciate the interplay between ideas and evidence in academic and media debateArgument and Evidence presents aspects of informal logic and statistical theory in a comprehensible way, enabling students to acquire skills in critical thinking which will outlast their undergraduate studies. Ideal as a companion for courses on met.